Comparative Study of Surgical Outcome of Linear Stapled Versus Manual Anastomosis Technique During Reversal of Loop Ileostomies - Aneeta Kumari, Rehmat Urf Sehrish Shah, Seema Shabbir, Ambreen Munir, Syed Asad Ali Shah, Suhail Ahmed Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the surgical outcomes of linear stapler versus manual anastomosis for the reversal of loop ileostomies Subjects and methods: This randomized control trial was conducted in the department of General Surgery at Liaquat University Hospital Jamshoro, from June 2018 to May 2019. All the patients with an age of 14 to 45 years of either gender, having typhoid perforation, and having undergone ileostomy in an emergency after 6–12 weeks of previous surgery were included. All patients were divided into two groups. Patients in group A were reversed with a linear stapler (LS), and the others were reversed through manual suturing (MS). Patients were followed for two weeks during Hospital stay and were discharged on clinically stable condition with normal bowel movements and no complication. Outcome was measured in terms of operative time, hospital stays, and postoperative complications in both groups. All the data was recorded in the predesigned proforma and analyzed by SPSS version 26. Results: A total of 218 patients were studied; the most common age group was 15–30 years in both groups, and males were in the majority in both groups. Anastomosis leakage occurred in 3.7% of patients in group A, while none was found in group B. The infection rate was significantly lower at 13.8% in group A compared to group B at 34.9% (p-0.001). Intestinal obstruction was observed in 1.8% of patients in group A compared to 8.3% in group B (p-0.002). Prolonged Hospital stay was significantly higher in group B (8.7%) (p- 0.001). Conclusion: It was concluded that stapler anastomosis is the safe, most reliable, and adaptable surgical tool for ileostomy reversal. It consumed very less operative time with very lower rate of complications and less time for follow-up as compared to manual suturing.